2019
DOI: 10.1021/acs.jafc.9b00846
|View full text |Cite
|
Sign up to set email alerts
|

Safety Assessment of Phytochemicals Derived from the Globalized South African Rooibos Tea (Aspalathus linearis) through Interaction with CYP, PXR, and P-gp

Abstract: Rooibos tea (Aspalathus linearis) is a well-known South African herbal tea enjoyed worldwide. Limited reports indicate the potential of rooibos tea to alter the activity of certain cytochrome P450 (CYP450) isozymes. In this study, the phytochemical investigation of MeOH extract of A. linearis (leaves and stems) resulted in the isolation and characterization of 11 phenolic compounds. The MeOH extract exhibited significant inhibition of the major human CYP450 isozymes (CYP3A4, CYP1A2, CYP2D6, CYP2C9, and CYP2C19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 51 publications
(93 reference statements)
0
18
0
Order By: Relevance
“…Thereafter, mass and retention time alignment and filter-by-frequency (features not present in at least one treatment in 100% of replications were discarded) were applied. However, when multiple annotations were possible, we selected those phenolic compounds previously identified in rooibos [30,31,32,33,34,35]. To achieve a higher degree of confidence in annotation, pooled samples were further analyzed in tandem mass spectrometry, using the previously reported conditions and a data-dependent MS/MS approach in place of the MS-only SCAN.…”
Section: Methodsmentioning
confidence: 99%
“…Thereafter, mass and retention time alignment and filter-by-frequency (features not present in at least one treatment in 100% of replications were discarded) were applied. However, when multiple annotations were possible, we selected those phenolic compounds previously identified in rooibos [30,31,32,33,34,35]. To achieve a higher degree of confidence in annotation, pooled samples were further analyzed in tandem mass spectrometry, using the previously reported conditions and a data-dependent MS/MS approach in place of the MS-only SCAN.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, earlier studies from our group [14,42] and others [32,43,44] have noted that dietary phytochemicals can exhibit dualfunctional behaviors concerning the modulation of xenobiotic metabolism and transport. In other words, phytochemicals may act as agonists for nuclear receptors like CAR, PXR, and AhR while also functioning as catalytic inhibitors for post-translationally matured proteins like CYPs and P-gp.…”
Section: Discussionmentioning
confidence: 78%
“…Literature surveys have shown that extracts from A. linearis have been reported to inhibit cell proliferation, thereby interfere with the growth of cancerous cells in the skin [ 56 ]. Furthermore, compounds (aspalathin and nothofagin) isolated from the methanol extract of A. linearis have also been reported to exhibit anticancer activity [ 57 ].…”
Section: Resultsmentioning
confidence: 99%